AGAMA DALAM PRAKTIS BUDAYA (SUATU TINJAUAN SOSIOLOGI AGAMA) - Ni Nyoman Dewi Astari Putri (UHN IGB Sugriwa Denpasar, 2021)
From the perspective of religion and culture, the phenomena foundin the society especially humans’ life are closely related to one another.This phenomenon is sometimes misunderstood by some people who do notunderstand how to place religious and cultural positions in people's lives.In human life, religion and culture do not stand alone or stand bythemselves, both have a very close relationship in their dialectics; alignedto create and then negate each other. Religion is a guideline for human lifethat is used as a reference in living their life, while culture is a habit or wayof human life that is created by humans themselves from the results ofcreativity, feeling, and intention given by God. Religion and cultureinfluence each other. Religion affects the culture, community groups, andethnic groups. However, culture tends to be fickle. This relationship hasimplications for the authenticity of religion, resulting in differentinterpretations. Religion is an idea that is idolized in every social action sothat society is always in balance and order of a stable system and structure.This condition can be expected to give rise to a serene and peaceful sociallife in which the function of religion becomes important and dominant. Inthis way, religion in turn truly places itself as a regulator of the traffic ofsocial obligations through its commands and prohibitions, and in it, societycannot refuse it. The point is that in recent times, since the 20th century,religion has become an attractive object for scientists and culture.